ANALISIS PERENCANAAN QUALITY ASSURANCE DITINJAU DARI ASPEK INPUT PELAYANAN KEPERAWATAN RAWAT INAP PASCA AKREDITASI PARIPURNA RS SWASTA X KOTA SEMARANG - Sarah Nurulita Fathanah Sukma; Sudiro Sudiro; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The quality assurance is program to monitor and asses the quality of service to consistent the standards. Input is the resource required to perform nursing service. As a plenary accredited hospital, the number of nursing personnel at hospital still not accordance the standard requirements, the lack of budget funds to fulfill the needs of the service, the service is still less controllable, the equipments has not been fulfilled in the service and the method has not been implemented fully by the nurse. The purpose of this research was to analyze the quality assurance planning reviewed from input aspects of inpatient nursing services post plenary accreditation. The type of research is observational with qualitative method and descriptive approach. The main informant i.e. nursing managers, head of the nursing profession, head of the logistics nursing, the chairman team of the quality of nursing and informant triangulations are three people of nursing coordinators. The data analysis used in this analysis with the steps: data reductions, data display, verification and conclusion drawing. The quality assurance planning reviewed from input aspects of inpatient nursing services are already done, but still potentially cause irregularities because of weak monitoring and evaluation systems. A double title of nurse resulted in an increase in the workload of nurses. The nursing departement has not noticed cadre recruitment of nurses. The Directors have not seen the complaint related to the tools needs of nurses in the room. Control of materials nursing services needed to avoid waste. Policies, guidelines and Standard Operational Procedures that are not in the regular monitoring, potentially not implemented by nurses. The hospital should complement the shortage of medical equipment and nursing services infrastructure, fulfill the standards the number of nurses, noting cadre recruitment of nurses, collaboration with the pharmaceutical and procurement to reschedule monitoring activity in regularly for keeping the standards accreditation plenary hospital.